2020
DOI: 10.35379/cusosbil.751018
|View full text |Cite
|
Sign up to set email alerts
|

Ri̇sk İştahinin Pay Geti̇ri̇leri̇ Üzeri̇ndeki̇ Etki̇si̇ni̇n İncelenmesi̇

Abstract: Bu çalışmanın amacı, finansal piyasalarda riskin bir göstergesi olarak ülkemizde Aralık 2008 tarihinden itibaren hesaplanan Risk İştahı Endeksinin (RİSE) pay getirileri üzerindeki etkisinin incelennmesidir. Yerli yatırımcılar için değişim metodu ile hesaplanan RİSE bağımsız değişken olarak kullanılmış ve BİST 100 endeksindeki değişim modele kontrol değişkeni olarak dâhil edilmiştir. Ocak 2009 -Ocak 2019 döneminde borsada işlem gören paylar, piyasa değerlerine göre sıralanmış ve en düşük piyasa değerine sahip %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
1
4
0
2
Order By: Relevance
“…According to Hatemi-J (2012) asymmetric causality test results, from the negative shocks in the RISE index to the negative shocks in the BIST Financial index, from the negative shocks in the RISE index to the positive shocks in the BIST Financial index, and from the positive shocks in the BIST Financial index to the positive shocks in the RISE index, a causal relationship was found from BIST Financial index negative shocks to negative shocks in the RISE index. The findings obtained in the study are similar to the studies conducted by Demirez & Kandır (2020) and Balat (2020), who concluded that risk appetite affects stock markets.…”
Section: Bulgularsupporting
confidence: 91%
See 3 more Smart Citations
“…According to Hatemi-J (2012) asymmetric causality test results, from the negative shocks in the RISE index to the negative shocks in the BIST Financial index, from the negative shocks in the RISE index to the positive shocks in the BIST Financial index, and from the positive shocks in the BIST Financial index to the positive shocks in the RISE index, a causal relationship was found from BIST Financial index negative shocks to negative shocks in the RISE index. The findings obtained in the study are similar to the studies conducted by Demirez & Kandır (2020) and Balat (2020), who concluded that risk appetite affects stock markets.…”
Section: Bulgularsupporting
confidence: 91%
“…The risk appetite index (RISE), which was prepared and published in cooperation with the Central Registry Agency and Özyeğin University in Turkey and calculated over weekly portfolio value changes for six different investor groups, was used as a risk appetite indicator in the studies (e.g. Saraç et al, (2016), Çelik et al, (2017), Fettahoğlu (2019), Demirez & Kandır (2020), Çifçi & Reis (2020), Kaplan (2020), Balat (2020) and Reis (2021)).…”
Section: Extended Abstractmentioning
confidence: 99%
See 2 more Smart Citations
“…After mentioning the theories in the literature, if we look at the field articles, it is seen that different subjects are mentioned by different researchers. Chen et al (2009) examined the performances of domestic and foreign investors in the Taiwanese stock market by using panel data analysis method; Bulut and Çoşkun (2015) investigated the effects of foreign direct investments on domestic investments with Granger causality analysis; Arora (2016) determined the relationship between domestic and foreign investors trading in the Indian stock market and stock returns; Sarac et al (2016) Demirez and Kandır (2020) investigated the relationship between the Risk Appetite Index (RISE) that representing domestic investors and stock returns.…”
Section: Extended Abstractmentioning
confidence: 99%